In vitro anti-tuberculosis activity of azole drugs against Mycobacterium tuberculosis clinical isolates - Imperiale, Belen Rocio; Cataldi, Angel Adrian; Morcillo, Nora (2018)
Background: Latent tuberculosis has been associated with the persistence of dormant Mycobacterium tuberculosis in the organism of infected individuals, who are reservoirs of the bacilli and the source for spreading the disease in the community. New active anti-TB drugs exerting their metabolic action at different stages and on latent/dormant bacilli are urgently required to avoid endogenous reactivations and to be part of treatments of multi- and extensively-drug resistant tuberculosis (M/XDR-TB). It was previously reported that azole drugs are active against M. tuberculosis. For that reason, the aims of this study were to determine the in vitro activity of azole drugs, imidazole (clotrimazole, CLO and econazole, ECO) and nitroimidazole (metronidazole, MZ and ipronidazole, IPZ), against a collection of MDR M. tuberculosis clinical isolates; and to analyze their potential use in both the LTB and the active forms of M/XDR-TB treatments. Methods: A total of 55 MDR M. tuberculosis isolates and H37Rv were included. MZ and IPZ activity against M. tuberculosis isolates were tested using anaerobic culture conditions. The activity of ECO and CLO was measured by the minimal inhibitory concentration (MIC) using a microdilution colorimetric method.